Incidence of spine surgery for degenerative and traumatic pathologies in patients with a history of cancer: a nationwide register-based study between 1997 and 2020 from Finland - Leevi A Toivonen; Ville Ponkilainen; Jussi P Repo; Ville M Mattila (Acta Orthopaedica, 2025)
Background and purpose: The number of cancer survivors has increased. Although spine surgery rates have multiplied in the general population, they are understudied in cancer populations. We aimed to determine the incidence rates of spinal surgery for degenerative and traumatic pathologies in patients with prior cancer. Our secondary aim was to define the underlying primary cancer diagnoses and survival rates after spinal procedures. Methods: Data was combined from 3 nationwide registers: the Finnish Cancer Register, Finnish Care Register for Health Care, and Finnish Cause of Death Register. Spine surgeries were identified using diagnosis and procedural codes, and tumor surgeries were excluded. Incidence rates were calculated per 100,000 inhabitants and adjusted for age and sex. Kaplan–Meier survival estimates (with 95% confidence intervals [CI]) were calculated per the first spine surgery. Results: 10,280 patients underwent 12,425 surgeries, with a mean age of 70 years; 53% were women. Degenerative pathologies accounted for 74% of the surgeries, followed by disc pathologies (20%) and trauma (6%). The incidence of spine surgeries increased from 3.7 to 15.1 per 100,000 person-years (300%) between 1997 and 2019. The increase mostly occurred in degenerative spine procedures (420%), whereas disc and trauma surgeries were temporally stable. The most common previously diagnosed cancers were breast (24%) and prostate (22%) cancers. All-cause survival after spine surgery was 94% (CI 94–95) at 1 year, and cancer-specific survival was 90% (CI 0.89–0.91) at 15 years. Conclusion: We showed a 300% increase in spine surgeries unrelated to cancer in patients with a history of cancer between 1997 and 2020. Survival rates remained favorable (94% [CI 0.89–0.91] at 1 year).